Technologies of Drilling Fluids of Various Degrees of Mineralization, Treated with Carboxymethylated Cellulose Ethers - M.K. Urozov; O.A. Toshbekov; O.Х. Кulmuminov; I.B. Boltayeva (International Journal on Orange Technologies, 2021)
Article shows the process of hydrolysis of polysaccharides with various by activity acids. By hydrolysis speed of these hydrolyzing agents was determined theirs active row, and shown that the hydrolysis of polysaccharides is advisable to carry out in environment of acetic acid.